2007
DOI: 10.2341/06-139
|View full text |Cite
|
Sign up to set email alerts
|

Sealing of Minimally Invasive Class II Fillings (slot) Using an Adhesive Patch: Sealant Margin Extension for Prevention

Abstract: ©Operative Dentistry, 2007, 32-5, 482-487 PR Schmidlin • R Seemann T Filli • T Attin • T Imfeld Clinical RelevanceThe sealing of minimally invasive restorations using a prefabricated adhesive patch significantly reduces leakage and caries formation. SUMMARYA laboratory study was performed to assess the potential of an adhesive patch to seal small, unbeveled, Class II, box-only (slot) composite fillings.After minimal access cavity preparation with an 80 µm diamond bur, 40 box-only Class II cavities were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Sealing of minimally invasive cavities using this device has already been shown to have the potential to significantly reduce caries formation and microleakage at filling margins. 16 The latter study has also shown that there was no undermining caries at the patch margins. In addition, the caries profile was not deeper as compared to the unprotected surrounding enamel.…”
mentioning
confidence: 83%
“…Sealing of minimally invasive cavities using this device has already been shown to have the potential to significantly reduce caries formation and microleakage at filling margins. 16 The latter study has also shown that there was no undermining caries at the patch margins. In addition, the caries profile was not deeper as compared to the unprotected surrounding enamel.…”
mentioning
confidence: 83%
“…It has been shown in vitro using a caries‐simulating chamber model that such a patch can completely inhibit de‐mineralization of the underlying enamel. The interproximal patch was also assessed for use in sealing small class II cavities and compared with unbeveled class II fillings that were filled with a hybrid resin in one increment (144). After exposure to thermo‐mechanical stress, practically no microleakage was found in the patch‐treated lesions, but dye penetration into dentin was observed in 50% of the filled lesions.…”
Section: Lesion Control With Micro‐invasive/minimally Invasive Measuresmentioning
confidence: 99%
“…Therefore, the concept of sealing occlusal surfaces of enamel lesions, has been transferred to smooth surfaces using surface sealants, infiltrants and patches. 7,8 Today, sealants are mostly used therapeutically on indication, attempting to arrest active noncavitated lesions. 9 While adhesive application or surface sealing acts as a diffusion barrier on the top of the lesion surface, the infiltration technique creates a barrier inside the lesion by replacing the mineral lost with a low-viscosity light-curing resin.…”
Section: Introductionmentioning
confidence: 99%
“…Use of an adhesive patch especially designed to seal smooth enamel surfaces, is another approach that has been developed for this purpose. 8,11 Additionally, other recently developed materials are nanotechnology liquid polishers. Their objective is to create a marginal seal with the ability to fill micro gaps and reduce micro leakage at composite margins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation